2015
DOI: 10.3174/ajnr.a4558
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous C-Arm Conebeam CT Angiography following Long-Term Flow-Diverter Implantation: Technologic Evaluation and Preliminary Results

Abstract: BACKGROUND AND PURPOSE:A noninvasive investigation with high spatial resolution and without metal artifacts is necessary for long-term imaging follow-up after flow-diverter implantation. We aimed to evaluate the diagnostic value of conebeam CT angiography with intravenous contrast enhancement in the assessment of vascular status following implantation of the Pipeline Embolization Device and to analyze the preliminary results of vascular status following long-term Pipeline Embolization Device implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the first study in which an alternative imaging technique has been shown to be comparable with DSA after FD treatment; in recent studies, contrast-enhanced MRA, [21][22][23] 3D TOF-MRA, 21,22 C-arm conebeam CT, 24,25 and CTA 22 were all inferior to DSA due to metal artifacts originating from the FD wires. Although a recent study comparing contrastenhanced MRA with DSA demonstrated good imaging of the aneurysm sac after FD treatment, the assessability of the stent lumen, however, remained difficult due to metal artifacts.…”
Section: Discussionmentioning
confidence: 82%
“…To our knowledge, this is the first study in which an alternative imaging technique has been shown to be comparable with DSA after FD treatment; in recent studies, contrast-enhanced MRA, [21][22][23] 3D TOF-MRA, 21,22 C-arm conebeam CT, 24,25 and CTA 22 were all inferior to DSA due to metal artifacts originating from the FD wires. Although a recent study comparing contrastenhanced MRA with DSA demonstrated good imaging of the aneurysm sac after FD treatment, the assessability of the stent lumen, however, remained difficult due to metal artifacts.…”
Section: Discussionmentioning
confidence: 82%
“…CBCT is a useful method in the evaluation of stent architecture, deployment, wall-apposition, and microvascular anatomy. 4,6,9,10 Contrast injection (either intravenous or intraarterial) is helpful to depict intrastent thrombus or endoleak. 3 Different percentages of contrast dilution ranging 10%-20% (10%-20% contrast media/80%-90% saline) have been adopted to avoid excess opacification of the parent vessel that may otherwise hamper proper visualization of the FD.…”
Section: Discussionmentioning
confidence: 99%
“…FPV-CTA protocols have been developed either without injection 5 or with diluted contrast material injection. 17,18 The major advantage of protocols with contrast material injection (IV or intra-arterial) is that they may help to depict intrastent thrombus or endoleak (ie, contrast media filing between the FDS and the inner wall of the parent artery) caused by incorrect apposition of the stent.…”
Section: Discussionmentioning
confidence: 99%
“…Such protocols have been used to evaluate the accuracy of the FDS deployment intraoperatively 4 and for follow-up imaging. 4,17 The potential of the visualization of the accurate deployment of FDS appears of tremendous importance owing to the fact that most intraoperative, postprocedure, or delayed complications, like thromboembolic events or even stent occlusion, seem to be related to FDS kinking or misdeployment. 19 In our series, we did not record any symptomatic ischemic complication caused by kinking or misdeployment of the FDS.…”
Section: Discussionmentioning
confidence: 99%